Food subsidies in Egypt: Benefit distribution and nutritional effects - Alderman, Harold (International Food Policy Research Institute, 1988)
On almost any street corner in Cairo one can buy a tamaya orfalafel sandwich for a few cents. This daily fare is a microcosm of the government's involvement in food pricing. The fava beans in the sandwich are subsidized. The oil in which they are fried is subsidized. The bread is subsidized. The tea one might have with the sandwich is subsidized, as is the sugar used to sweeten it. Furthermore, the sandwich will probably be wrapped in a newspaper that is likely to contain a speech or an editorial on the subsidy system.